MTHFR and MTRR genotype and haplotype analysis and colorectal cancer susceptibility in a case-control study from the Czech Republic - Pardini, Barbara; Kumar, Rajiv; Naccarati, Alessio; Prasad, Rashmi B; Forsti, Asta; Polakova, Veronika; Vodickova, Ludmila; Novotny, Jan; Hemminki, Kari; Vodicka, Pavel (Mutation research, 2011)
Polymorphic variants in genes involved in one-carbon metabolism, in particular of dietary folate, may modulate the risk for colorectal cancer through aberrant DNA-methylation and altered nucleotide synthesis and repair. In the present study, we have assessed the association of six polymorphisms and relative haplotypes in the MTHFR gene (rs1801133 and rs1801131) and in the MTRR gene (rs1801394, rs1532268, rs162036, and rs10380) with the risk for colorectal cancer in 666 patients and 1377 controls from the Czech Republic. We found that the 677 C>T polymorphism in the MTHFR gene significantly decreased the risk for colorectal cancer in homozygous carriers of the variant allele (OR, 0.58; 95% CI, 0.39-0.87). Also, we noted a significantly different distribution of genotypes between cases and controls for the 66A>G polymorphism in the MTRR gene. In particular, homozygous carriers of the G-containing allele of this polymorphism were at an increased risk for colorectal cancer (OR, 1.39; 95% CI, 1.04-1.85). Haplotype analysis of the two MTHFR polymorphisms showed a moderate difference in the distribution of the TA haplotype between cases and controls. In comparison to the most common haplotype (CA), the TA haplotype was associated with a decreased risk for colorectal cancer (OR, 0.84; 95% CI, 0.71-0.99). No difference in the distribution between cases and controls was observed for the haplotypes based on the four polymorphisms in the MTRR gene. The present study suggests that the 677TT genotype and the TA haplotype in the MTHFR gene may also have a role in colorectal cancer risk in the Czech population, indicating the importance of genes involved in folate metabolism with respect to cancer risk. For MTRR, additional studies on larger populations are needed to clarify the possible role of variation in this gene in colorectal carcinogenesis.
Keywords: dospělí; Ferredoxin-NADP Reductase; kolorektální nádory; Genotype; Female; Adult; ženské pohlaví; jednonukleotidový polymorfismus; Colorectal Neoplasms; lidé; Polymorphism, Single Nucleotide; genotyp; genetická predispozice k nemoci; Aged, 80 and over; studie případů a kontrol; Genetic Predisposition to Disease; Methylenetetrahydrofolate Reductase (NADPH2); Male; Case-Control Studies; Aged; Czech Republic; Haplotypes; ferredoxin-NADP-reduktasa; Česká republika; lidé středního věku; senioři nad 80 let; senioři; haplotypy; mužské pohlaví; Middle Aged; methylentetrahydrofolátreduktasa (NADPH2); Humans